The organisational performance of national disability sport organisations during a time of austerity: a resource dependence theory perspective - Brown, C.; Pappous, A. (International Journal of Sport Policy and Politics, 2018)
Austerity measures implemented by the UK Coalition government have had a negative impact on disabled people. This article utilises the resource dependence theory to explore the challenges national disability sport organisations (NDSOs) have faced in their attempts to achieve growth, whilst discussing some of the tactics used to overcome these challenges. Secondary quantitative data from the 2011-2015 NDSO accounts were analysed, which suggests that increased income has been accompanied by increased cost, with fluctuations between surpluses and deficits across the financial years. Funding from Sport England, the government body for grassroots sport in England, was either awarded for the first time or increased. Nine in-depth interviews were conducted with senior managers from seven NDSOs, the English Federation of Disability Sport, and Sport England. It was found austerity presented challenges for the NDSOs in accessing charitable grants and funding and that some disabled people were fearful of losing their disability benefits if they were seen to be active. The management of relationships with national governing bodies and county sport partnerships was also a challenge. The formation of alliances, the building up of financial reserves and the generation of knowledge have been some of the tactics used by the NDSOs in the management of their resources. This research highlights how some NDSOs have achieved growth amid an uncertain economic backdrop, and how these organisations have managed their scarce resources.